A multi-stage activated carbon impregnation system: Isotherms, kinetics and multi-objective modeling optimization. (14th December 2020) - Hu, Jian; Zhang, Qi; He, Chang; Chen, Qing L.; Qi, Zhiwen; Li, Qingen; Zhang, Bing J.
Graphical abstract: Highlights: A multi-stage activated carbon impregnation system is introduced. Columnar activated carbon adsorption isotherm and kinetic models are well regressed. A multi-objective nonlinear programming optimization framework is presented. The specific solute consumption is decreased by 65.11%. The specific operating time is decreased by 85.88%. Abstract: A multi-stage activated carbon impregnation system, with a special emphasis on solvent reuse, is introduced and optimized in this study. Experiments and modeling optimization are combined to simultaneously minimize the solute consumption and operating time for the system. The adsorption isotherm and kinetic models are well regressed based on a series of experiments on activated carbon impregnated in triethylene tetramine solution. A multi-objective nonlinear programming optimization framework is then formulated based on the regressed isotherm and kinetic models and material balance, including activated carbon, solute, water and impurities at each stage in the system. The AUGMECON method and global solver ANTIGONE are used to solve the challenging optimization problem, and the pareto optimal solutions are obtained. Additionally, a new dimensionless number is presented to further coordinate the operating parameters for the system. The result shows that the specific solute consumption and operating time are decreased by 65.11% and 85.88%, respectively.